Exploring the roles of ncRNAs in prostate cancer via the PI3K/AKT/mTOR signaling pathway - Guo, Rongwang; Shi, Liji; Chen, Yonghui; Lin, Canling; Yin, Weihua (Frontiers in Immunology, 2025)
Although various treatment options are available for prostate cancer (PCa), including androgen deprivation therapy (ADT) and chemotherapy, these approaches have not achieved the desired results clinically, especially in the treatment of advanced chemotherapy-resistant PCa. The PI3K/AKT/mTOR (PAM) signaling pathway is a classical pathway that is aberrantly activated in cancer cells and promotes the tumorigenesis, metastasis, resistance to castration therapy, chemoresistance, and recurrence of PCa. Noncoding RNAs (ncRNAs) are a class of RNAs that do not encode proteins. However, some ncRNAs have recently been shown to be differentially expressed in tumor tissues compared with noncancerous tissues and play important roles at the transcription and posttranscription levels. Among the types of ncRNAs, long noncoding RNAs (lncRNAs), microRNAs (miRNAs), circular RNAs (circRNAs), and Piwi-interacting RNAs (piRNAs) can participate in the PAM pathway to regulate PCa growth, metastasis, angiogenesis, and tumor stemness. Therefore, ncRNA therapy that targets the PAM signaling pathway is expected to be a novel and effective approach for treating PCa. In this paper, we summarize the types of ncRNAs that are associated with the PAM pathway in PCa cells as well as the functions and clinical roles of these ncRNAs in PCa. We hope to provide novel and effective strategies for the clinical diagnosis and treatment of PCa.